Environmental sustainability and agenda 2030 : efforts, progress and prospects - Tauringana, Venancio; Moses, Olayinka (Advances in environmental accounting & management ;, 2022)
Actions to accomplish Agenda 2030 have gained propulsion across time yet remain undetermined in several respects. This volume draws attention to environmental-related Sustainable Development Goals (SDGs) and the progress of implementation at country and company levels, underscoring the urgent actions needed. Environmental Sustainability and Agenda 2030: Efforts, Progress & Prospects documents the status of environmental SDG implementation in the two developing blocs of BRICS and MINTS, highlighting the reporting practices across these countries. Contributors illustrate that multi-stakeholder participation using group model-building exercises can be practically helpful to generate a shared mental model of multiple stakeholders in conflict. Further insights with practical implications for managers and policy makers include mechanisms for managing modern slavery through corporate social reporting practices, minimising slavery in domestic and global supply chains; use of sustainability accounting in accomplishing Agenda 2030; corporate motivation for disclosing clean water and sanitation (SDG-6) related actions; and the state of corporate environmental reporting research in sub-Saharan Africa.